ANALISA DAN IMPLEMENTASI JARINGAN WIRELESS MAC ADDRESS MENGGUNAKAN FILTERING PADA PT. FAYA KUNTURA AGUNG KONSULTINDO - Dipo Era Ginanti; Ade Christian; Taopik Hidayat (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2022)
The evolution of this era is become advancing as well for Technology Information and Telecommunications. This evolution has been explored in Wireless Technology, even in all devices such as smartphones, tablets and laptops can use it. The Internet has tremendously impacted culture and it become a daily necessity by people in the world, as the internet can support the process of communicating, learning, and data transfer. Places that use wireless networks have started a lot such as schools, universities, and companies. Yet, wireless networks still have security that is quite vulnerable because it can be misused by other parties. To minimize this problem we can use MAC Address Filtering. MAC Address Filtering is a technique for prevents access to a network if the MAC Address of the devices attempting to connect does not match any addresses marked as allowed. MAC Address Filtering has 2 tasks of verification so before it does filtering, the user must log in first using the MAC Address that has been registered and then enter the username and password if it matches the MAC Address then the login will be successful, otherwise, it will be rejected. This wireless MAC Address Filtering security can avoid hackers who can enter the wireless network which makes a slow network.